2019
DOI: 10.1002/jor.24441
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of COX‐2 Pathway as a Potential Prophylaxis Against Arthrofibrogenesis in a Rabbit Model of Joint Contracture

Abstract: Arthrofibrosis is a common complication following total knee arthroplasty caused by pathologic fibroblast activation and excessive collagen deposition around a synovial joint leading to debilitating loss of motion. Treatment options are limited because the pathologic mechanisms remain to be characterized. Dysregulation of the inflammatory cascade may lead to communication between myofibroblasts and immune cells triggering tissue metaplasia, and excessive collagen deposition described clinically as arthrofibros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 45 publications
7
41
0
Order By: Relevance
“…The range of tissue findings on both H&E and α-SMA staining Outcomes of the present study corroborate previous results from our group demonstrating decreased contracture severity after intra-articular administration of the COX-2 inhibitor CXB via repeated intra-articular injections. 10 In the current study, we identified decreased COL3A1, COL6A1, and ACTA2 mRNA expression in all treatment arms when compared to the contracture control group (group 1). We hypothesize that this likely results from early inhibition of the pro-inflammatory cascade and continues during the collagen membrane absorption phase (which has been reported to take approximately 8 weeks).…”
Section: Histopathology Datasupporting
confidence: 55%
See 4 more Smart Citations
“…The range of tissue findings on both H&E and α-SMA staining Outcomes of the present study corroborate previous results from our group demonstrating decreased contracture severity after intra-articular administration of the COX-2 inhibitor CXB via repeated intra-articular injections. 10 In the current study, we identified decreased COL3A1, COL6A1, and ACTA2 mRNA expression in all treatment arms when compared to the contracture control group (group 1). We hypothesize that this likely results from early inhibition of the pro-inflammatory cascade and continues during the collagen membrane absorption phase (which has been reported to take approximately 8 weeks).…”
Section: Histopathology Datasupporting
confidence: 55%
“…5 In addition, significant differences were detected in the messenger RNA (mRNA) expression of collagen markers COL1A1, COL3A1, and COL6A1 (Figure 4) within periarticular soft tissues near the surgically manipulated joint, as has been noted previously. 10 However, COL1A1…”
Section: Genetic Expressionmentioning
confidence: 99%
See 3 more Smart Citations